The Role of Banking Finance in Developing Housing Sector: Case study of Real Estate Commercial Bank- Sudan (2011- 2018) - Omer, Omer Alla Gabo; Nasreldin, Khalid Abdulla (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aims to clarify the role of banking finance on developing housing sector in Sudan (2011- 2018). Descriptive analytical and case study approaches were used. The study reached several results, including a weak contribution (4%- 14%) of commercial banks in financing housing sector due to restriction of granting real estate finance. Moreover, political instability and miss- management of public resources have contributed to the failing of some economic and social projects. Nevertheless, Real Estate Commercial Bank (RECB) played a vital role in developing the housing sector through financing, constructing and rehabilitation of some housing projects. The study recommended to increase the capital of RECB and real estate financing ratio to enable it to provide housing and public services such as electricity, water stations and schools especially for people with low- income. Also, the state should take into consideration designing housing plans and banking policies that support housing sector to enable it to meet population growth.
Keywords: bank financing; real estate bank; housing; Sudan